Development of a method for measuring mass concentration of cyanides in soil samples using gas chromatography and tandem mass-selective detection - D. O. Korneev; M. A. Ponsov; A. A. Rodionov; L. V. Petrakova; I. V. Rybalchenko (Вестник войск РХБ защиты, 2020)
The Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on Their Destruction places CN-containing toxic chemicals like tabun and its numerous homologues and analogues (around 10.000 organic compounds), hydrogen cyanide, cyanogen chloride etc., under the international control in the field of arms control, disarmament and non-proliferation. Moreover, CN-containing toxic chemicals are hazardous industrial and environmental pollutants. Soils are the most widely-spread and complex environmental objects for the detection and analysis of cyanides. The aim of this work is to elaborate the method for measuring mass concentration of cyanides in soil samples, which is more sensitive and less labor-intensive, than photometric method, adopted in the Russian Federation. The developed method involves the use of 2,3,4,5,6-pentafluorobenzyl bromide as a derivatizing agent and GC/MS/MS with methane negative ion chemical ionization. It enables the identification and quantification of cyanide ions in soil in the range of 0.7 ng/g – 10.0 μg/g. This method is much more sensitive than the photometric method, included in the federal registry. It does not require the use of potassium cyanide isotopes with radioactive labels of carbon and potassium as an internal standard, and it requires less implementation time.